Laser pulse propagation and enhanced energy coupling to fast electrons in dense plasma gradients - R J Gray; D C Carroll; X H Yuan; C M Brenner; M Burza; M Coury; K L Lancaster; X X Lin; Y T Li; D Neely; M N Quinn; O Tresca; et al. (New Journal of Physics, 2014)
Laser energy absorption to fast electrons during the interaction of an ultra-intense (10 ^20 W cm ^−2 ), picosecond laser pulse with a solid is investigated, experimentally and numerically, as a function of the plasma density scale length at the irradiated surface. It is shown that there is an optimum density gradient for efficient energy coupling to electrons and that this arises due to strong self-focusing and channeling driving energy absorption over an extended length in the preformed plasma. At longer density gradients the laser filaments, resulting in significantly lower overall energy coupling. As the scale length is further increased, a transition to a second laser energy absorption process is observed experimentally via multiple diagnostics. The results demonstrate that it is possible to significantly enhance laser energy absorption and coupling to fast electrons by dynamically controlling the plasma density gradient.